Highly efficient 1D p-Te/2D n-Bi2Te3 heterojunction self-driven broadband photodetector - Zhao, Chenchen; Wang, Dongbo; Cao, Jiamu; Zeng, Zhi; Zhang, Bingke; Pan, Jingwen; Liu, Donghao; Liu, Sihang; Jiao, Shujie; Chen, Tianyuan; Liu, Gang; Fang, Xuan; et al. (Nano research, 2024)
Broadband photodetectors with self-driven functions have attracted intensive scientific interest due to their low energy consumption and high optical gain. However, high-performance broadband self-driven photodetectors are still a significant challenge due to the complex fabrication processes, environmental toxicity, high production costs of traditional 3D semiconductor materials and sharply raised contact resistance, severe interfacial recombination of 2D materials and 2D/3D mixed dimension heterojunction. Here, 1D p-Te/2D n-Bi 2 Te 3 heterojunctions are constructed by the simple and low-cost hydrothermal method. 1D p-Te/2D n-Bi 2 Te 3 devices are applied in photoelectrochemical (PEC) photodetectors, with their high performance attributed to the good interfacial contacts reducing interface recombination. The device demonstrated a broad wavelength range (365–850 nm) with an/ ph // dark as high as 377.45. The R i D *, and external quantum efficiency ( EQE ) values of the device were as high as 12.07 mA/W, 5.87 × 10 10 Jones, and 41.05%, respectively, which were significantly better than the performance of the prepared Bi 2 Te 3 and Te devices. A comparison of the freshly fabricated device and the device after 30 days showed that 1D p-Te/2D n-Bi 2 Te 3 had excellent stability with only 18.08% decay of photocurrent. It is anticipated that this work will provide new emerging material for future design and preparation of a high-performance self-driven broadband photodetector.